Analysis of Incidence Rate in Inpatience Based on Patient Safety Targets Mitra Medika Hospital Bandar Klippa - Aida Sulisna; Dilla Fitria; Sri Agustina Meliala; Hana Dhini Julia Pohan (Pena Cendekia Insani, 2022)
Introduction : Patient safety incidents are unintentional events and conditions that have the potential to result in preventable injury to patients so that patient safety incidents can affect the incident rate in hospitalization. Objective: To identify and analyze the incidence rate in the inpatient unit based on patient safety goals in the Hospital from 6 (six) patient safety goal elements. Method: The type of research used is quantitative with a cross sectional approach. The population and sample in this study used a saturated sampling technique with a total of 80 respondents. Results: Research using the chi square test includes identifying patients correctly with a p-value of 0.002 <0.05, increasing effective communication with a p-value of 0.002 <0.05, increasing drug safety needs to be watched out for with a p-value of 0.046 <0 .05, ensuring the correct location and surgical procedure in the patient with a p-value of 0.444 > 0.05, reducing the risk of infection related to health services has a p-value of 0.166 > 0.05, reducing the risk of injury to patients due to falls with a p-value of 0.016 < 0.05, against the incidence rate in hospitalization. Conclusion: There is an influence between the variables identifying the patient correctly, increasing effective communication, increasing drug safety needs to be watched out for, and reducing the risk of patient injury due to falls on the incidence rate in hospitalization and there is no influence between ensuring the location and surgical procedure in the correct patient, Reducing the risk of health care-associated infection to the incidence rate in hospitalization. Suggestions that can be given are SPO socialization and training for nurses in inpatients related to patient safety goals and communication and collaboration between teams are always improved in service.